The Effectiveness of Musyarakah Contracts for Bank Syariah Indonesia Customers in Sharia-Based UMKM Financing - Ranisa Tabar; Hikmatul Mufarrohah; Ridwan Hasanudin; Muhamad Ibnu Malik (Kawakib: Journal of Multidisciplinary Research, 2025)
Micro, Small, and Medium Enterprises play a vital role in Indonesia’s economy but often face challenges in accessing financing. This study aims to examine the effectiveness of the Musyarakah contract in financing UMKM at Bank Syariah Indonesia (BSI) and to identify the factors influencing its success. A qualitative approach with a descriptive-analytical method was employed, using interviews, observations, and document analysis for data collection. Primary data were collected from BSI UMKM customers, while secondary data were obtained from relevant literature. Data analysis included data reduction, systematic presentation, and conclusion drawing. The results indicate that the Musyarakah contract enhances UMKM performance and sustainability by promoting collaboration, profit-sharing, and fairness. Its effectiveness is influenced by managerial capacity, customer understanding of profit-sharing mechanisms, Islamic banking regulations, and market conditions. Key challenges, such as high business risks and limited customer knowledge, can be addressed through Sharia-based financial education and intensive mentoring. This study confirms that Musyarakah-based financing has strategic potential to strengthen UMKM development and support the growth of Indonesia’s Islamic economy.